Making Austerity Popular: The Media and Mass Attitudes toward Fiscal Policy. Issue 2 (25th March 2018) - Barnes, Lucy; Hicks, Timothy
Abstract: What explains variation in individual attitudes toward government deficits? Although macroeconomic stance is of paramount importance for contemporary governments, our understanding of its popular politics is limited. We argue that popular attitudes regarding austerity are influenced by media (and wider elite) framing. Information necessary to form preferences on the deficit is not provided neutrally, and its provision shapes how voters understand their interests. A wide range of evidence from Britain between 2010 and 2015 supports this claim. In the British Election Study, deficit attitudes vary systematically with the source of news consumption, even controlling for party identification. A structural topic model of two major newspapers' reporting shows that content varies systematically with respect to coverage of public borrowing—in ways that intuitively accord with the attitudes of their readership. Finally, a survey experiment suggests causation from media to attitudes: deficit preferences change based on the presentation of deficit information.